Enhancing English Speaking Competence Using The Cake App: Infographics as the Innovative Guidances for Teaching Speaking in Tourism Contexts - Damayanti, Made Regina Miranda; Utami, I.G.A. Lokita Purnamika; Agustini, Dewa Ayu Eka (PROJECT (Professional Journal of English Education), 2025)
The teacher's role as a learning process facilitator requires using appropriate tools to assist students in learning faster and to engage them better. In light of recent developments in educational technology, incorporating digital learning tools appears to be an intriguing approach. Nevertheless, not all teachers are familiar with and might be inexperienced with such digital learning tools that still require guidance in utilizing them to design their English-speaking lessons. One of those tools that can assist learners in improving their English competencies, specifically speaking as the notably challenging aspects of language proficiency is the Cake App. This study intended to develop infographics of the Cake App-based teaching speaking ideas for teaching 12th-grade tourism vocational high school students, in which one English teacher was involved as the research subject. This Design and Development study employed the DDE model (Richey & Klein, 2014), using a quantitative technique to analyze the data. The judgments indicated that the infographics were categorized as ‘excellent products,’ with content evaluations obtaining a percentage of 89% and 91%, including media and design evaluations achieving 90% and 95%. Furthermore, the participating teacher noted that the Cake App offered a novel approach to utilizing a real-world tool for speaking instruction.